Determination of d- and l-Amino Acids in Garlic Foodstuffs by Liquid Chromatography–Tandem Mass Spectrometry - Mayu Onozato; Haruna Nakanoue; Tatsuya Sakamoto; Maho Umino; Takeshi Fukushima (Molecules, 2023)
Black garlic is currently attracting interest as a health food and constituent of commercial supplements; however, no data regarding the d-amino acids within black garlic have been reported. Therefore, the amino acid compositions of methanol extracts from fresh and black garlic were compared herein. We investigated the contents of the d- and l-forms of amino acids in commercial fresh, black, and freeze-dried garlic foodstuffs by liquid chromatography–tandem mass spectrometry (LC–MS/MS) using a pre-column chiral derivatization reagent, succinimidyl 2-(3-((benzyloxy)carbonyl)-1-methyl-5-oxoimidazolidin-4-yl) acetate. Several d-amino acids, namely, the d-forms of Asn, Ala, Ser, Thr, Glu, Asp, Pro, Arg, Phe, Orn, Lys, and Tyr, were observed in the methanol extract of black garlic, whereas only d-Ala was detected in that of fresh garlic foodstuffs. These data suggest that several d-amino acids can be produced during fermentation for preparing black garlic.